Sosialisasi Komunikasi Kelompok Wanita Tani Prabumulih dalam Menguatkan Engagement Anggota Kelompok - Rama Sanjaya; Catherine Wahyuning Wilujeng; A. Rachman Para Buana; Etika Oktasari; Kurdeniansyah Kurdeniansyah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Community empowerment involving Kelompok Wanita Tani (Women Farmer Groups) represents an environmentally conscious agricultural empowerment initiative implemented as part of a Corporate Social Responsibility (CSR) program. In Tanjung Menang Village, Prabumulih. This empowerment effort was initiated by the Community Involvement and Development (CID) Team of PT Pertamina EP Limau Field in collaboration with academic partners engaged two hundred fifty of people and classify in eight Women Farmer Groups from the village. Group communication served as a key mechanism to strengthen engagement among members, aiming to enhance their psychological well-being and serve as an indicator of sustainable community empowerment. Data collection followed the standard criteria established by the CID Pertamina EP Limau Field team including participant profiling and characterization. The implementation methods included observation, interviews, focus group discussions, and direct interaction. Findings indicated that effective group communication significantly contributes to individual empowerment levels and can be applied both internally and externally to foster strong, sustainable group relations.